Improving The Interpersonal Intelligence Of 5-6 Year-Old Children Through Water Relay Playing At Al-Hidayah 1 PAUD In The 2024/2025 Academic Year - Sapitri, Ardila; Marzoan, Lalu; Alawiyah, Tuti (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Abstract. The purpose of this research is to understand how water relay activities can enhance the interpersonal intelligence of children aged 5-6 years at PAUD Al-Hidayah 1 Rempek Darussalam. The research method used is classroom action research (CAR) with the Milles and Huberman research model, utilizing data collection techniques such as observation, interviews, and documentation. Based on the research findings and observations conducted from the pre-cycle, cycle I, and cycle II, there is an indication of change or improvement in the interpersonal intelligence abilities of children aged 5-6 years through playing water relay. This serves as evidence that there is a positive impact resulting from the learning done through water relay activities, as seen in the pre-cycle session where only 4 children achieved scores of 70-72%, which did not meet the classical completeness expected by the researcher, From the graph above, it shows that the majority of children received scores in the categories of Starting to Develop (MB) and Not Developing (BB). Then in Cycle I, there was an increase in children's interpersonal intelligence skills, which developed as expected (BSH) with 9 children or 50%, and there were also some children who had not yet reached the target expected by the researcher, which was still in the stage of Starting to Develop (MB) with 6 children or 33.3%. Meanwhile, in Cycle II, there was another increase, with 15 children or 83.3% meeting the criteria for completion and the remaining 3 children or 16.7% did not meet the criteria. Keywords: Interpersonal Intelligence, Water Relay Play, Early Childhood